Effect of structural instability on creep of zirconium subjected to severe plastic deformation - Frolov, V.A; Sokolenko, V.I.; Matz, A.V.; Karaseva, E.V. (Вопросы атомной науки и техники, 2014)
The peculiarities creep and electro-physical characteristics of zirconium subjected to severe plastic deformations by rolling on the different degrees at 300 K was studied. It is shown that in the process of creep of zirconium due to changes in the conditions of deformation the structure, which was created by rolling, becomes unstable. A plastic flow is carried out because of structure rearrangement at joint action of several mechanisms and accompanied by stress relaxation.